Nucleoporin Nup188 is required for chromosome alignment in mitosis. Issue 7 (2nd May 2013) - Itoh, Go; Sugino, Shiro; Ikeda, Masanori; Mizuguchi, Mayumi; Kanno, Shin‐ichiro; Amin, Mohammed A.; Iemura, Kenji; Yasui, Akira; Hirota, Toru; Tanaka, Kozo
Abstract : Most cancer cells are aneuploid, which could be caused by defects in chromosome segregation machinery. Nucleoporins (Nup) are components of the nuclear pore complex, which is essential for nuclear transport during interphase, but several nucleoporins are also known to be involved in chromosome segregation. Here we report a novel function of Nup188, one of the nucleoporins regulating chromosome segregation. Nup188 localizes to spindle poles during mitosis, through the C‐terminal region of Nup188. In Nup188‐depleted mitotic cells, chromosomes fail to align to the metaphase plate, which causes mitotic arrest due to the spindle assembly checkpoint. Both the middle and the C‐terminal regions were required for chromosome alignment. Robust K‐fibers, microtubule bundles attaching to kinetochores, were hardly formed in Nup188‐depleted cells. Significantly, we found that Nup188 interacts with NuMA, which plays an instrumental role in focusing microtubules at centrosomes, and NuMA localization to spindle poles is perturbed in Nup188‐depleted cells. These data suggest that Nup188 promotes chromosome alignment through K‐fiber formation and recruitment of NuMA to spindle poles.